The strange woman [videorecording (DVD)] - Ulmer, Edgar G. (Edgar George), 1904-1972; Lamarr, Hedy, 1913-2000; Sanders, George, 1906-1972; Hayward, Louis, 1909-1985; Stromberg, Hunt, 1894-1968 (Film Chest, 2014)
Lamarr plays a shrewish woman in early 19th-century Maine who schemes for the favors of three rich men.